2020
DOI: 10.1111/jam.14700
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbapenem‐resistant Klebsiella pneumoniae in a tertiary hospital in Fuzhou, China

Abstract: Aims: The emergence of carbapenem-resistant Klebsiella pneumoniae (CRKP) strains has led to increased mortality and morbidity rates. Tigecycline, a new class of broad-spectrum glycyl-tetracycline antibiotics, has been used to target multi-and pan-drug-resistant bacterial infections. This study aimed to assess the molecular characteristics of CRKP in a tertiary hospital, and its susceptibility to tigecycline, to create a reference for hospital infection control and clinical drug use. Methods and Results: We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
3
3
0
1
Order By: Relevance
“…Respiratory tract infections were the most common source of isolation, which agrees with the results reported by Chen et al in China [ 27 ]. In this study, CRE strains were mainly isolated in the neurosurgery (25%), intensive care unit (ICU; 16.8%), neurology (10%), and respiratory (6.9%) wards.…”
Section: Discussionsupporting
confidence: 90%
“…Respiratory tract infections were the most common source of isolation, which agrees with the results reported by Chen et al in China [ 27 ]. In this study, CRE strains were mainly isolated in the neurosurgery (25%), intensive care unit (ICU; 16.8%), neurology (10%), and respiratory (6.9%) wards.…”
Section: Discussionsupporting
confidence: 90%
“…In China, it has been reported that the presence of KPC is responsible for carbapenem resistance in adult and pediatric isolates. 25 , 42 The present work demonstrated that the NDM and KPC genes detected in CRKP were mainly isolated in children and adults, respectively. Although OXA-48 is a prevalent carbapenemase type associated with Kp in some European countries, such as France and Turkey, 43 , 44 it is seldom detected in Kp isolates in China, 45 , 46 and the present study further support the observation that OXA-48 is not currently the primary carbapenemase types associated with Kp in China.…”
Section: Discussionsupporting
confidence: 52%
“…In the past, many common antibiotics can be selected for the treatment of Klebsiella pneumoniae pneumonia, such as ciprofloxacin, tobramycin, and cephalosporin, which have satisfactory bactericidal effects and can achieve significant clinical effects [15][16][17]. With the advent of broad-spectrum and high-efficiency antibiotics and excessive use, bacterial resistance has become stronger and more pan-resistant strains, especially the large-scale use of third and fourthgeneration cephalosporins and carbapenem antibiotics.…”
Section: Discussionmentioning
confidence: 99%